Occupational Heat Stress and Practical Cooling Solutions for Healthcare and Industry Workers During the COVID-19 Pandemic. Issue 9 (21st September 2020) - Foster, Josh; Hodder, Simon G; Goodwin, James; Havenith, George
Abstract: Treatment and management of severe acute respiratory syndrome coronavirus-2, which causes coronavirus disease (COVID-19), requires increased adoption of personal protective equipment (PPE) to be worn by workers in healthcare and industry. In warm occupational settings, the added burden of PPE threatens worker health and productivity, a major lesson learned during the West-African Ebola outbreak which ultimately constrained disease control. In this paper, we comment on the link between COVID-19 PPE and occupational heat strain, cooling solutions available to mitigate occupational heat stress, and practical considerations surrounding their effectiveness and feasibility. While the choice of cooling solution depends on the context of the work and what is practical, mitigating occupational heat stress benefits workers in the healthcare and industrial sectors during the COVID-19 disease outbreak.